Factors influencing eating behavior of Benghazi University students - Souad Farag El-Mani; Reima M. Mansour; Amna E Abdessamad; Etchomaly A. Al-Abbar; Nour Shallouf; Randa Amer (Asian Journal of Medical Sciences, 2020)
Background: University students are more exposed to new individual and environmental influences. This transition period is considered as a risky life phase because it’s characterized by changing in physical and social status as well as changing in the lifestyle that will affect the eating behavior of students.